Waiting for snow in Havana : confessions of a Cuban boy - Eire, Carlos M. N. (Free Press, 2004)
Waiting for Snow in Havana is both an exorcism and an ode to a paradise lost. For the Cuba of Carlos<U+2019>s youth<U+2014>with its lizards and turquoise seas and sun-drenched siestas<U+2014>becomes an island of condemnation once a cigar-smoking guerrilla named Fidel Castro ousts President Batista on January 1, 1959. Suddenly the music in the streets sounds like gunfire. Christmas is made illegal, political dissent leads to imprisonment, and too many of Carlos<U+2019>s friends are leaving Cuba for a place as far away and unthinkable as the United States. Carlos will end up there, too, and fulfill his mother<U+2019>s dreams by becoming a modern American man<U+2014>even if his soul remains in the country he left behind. Narrated with the urgency of a confession, Waiting for Snow in Havana is a eulogy for a native land and a loving testament to the collective spirit of Cubans everywhere.